Supporting communication among cognitive robots in simulated environments - Devalle, Jesica (2011)
Despite the fact that the Khepera II is an experimental platform widely used in the scientific community related to robotics research, its application to cognitive robotics is not as extensive as it should be. Particularly, in this field of research, the Khe-DeLP framework has arisen as an interesting proposal for developing cognitive agents to control real and simulated Khepera II robots. Although Khe-DeLP allows to work with multiple robots within the same environment, at present, only nonintentional communication among them can be achieved in this framework. Therefore, in this work we present extentions to Khe-DeLP to be able to model simulated scenarios where multiple robots interact by using explicit communication among them. This new feature improves Khe-DeLP since any kind of coordination problems can be simulated within the framework. As concept test, an example is presented which aims to validate coordinated behaviours of the robots by using the new communication features included in Khe-DeLP.